Survey the Effects of Partial Root Zone Deficit Irrigation and Deficit Irrigation on Quantitative, Qualitative and Water Use Efficiency of Pomegranate - mohammad saeed tadaion; Gholamreza Moafpourian (Majallah-i ̒Ulum-i Bāghbānī, 2017)
Introduction: One of the latest efficient methods on increment of water use efficiency that confirmed by many scientists all over the world is deficit and alternative partial root zone deficit irrigation. In this experiment the effect of deficit and alternative partial root zone deficit irrigation on fruit yield, quality and water use efficiency of pomegranate (Punicagranatum (L.) cv. Zarde-anar) were investigatedin Arsenjan semi-arid region. Materials and Methods: The experiment was carried out in a constant plots and randomized complete block design (RCBD) with four replicationsin five years.Treatmentswere 1- full flood irrigation (100 percent crop water requirement) (T1) 2- flood irrigation with 100 percent crop water requirement as alternate partial root-zone irrigation(every irrigation conducted on one side of tree) (T2) 3- flood irrigation with 50 percent crop water requirement as regular deﬁcit irrigation (T3) 4- full two-side drip irrigation(with regard to crop water requirement) (eight drippers with twolit/hour flow by two different individual networks) (T4) 5- alternate partial root-zone drip irrigation with 100 percent crop water requirement (T5) 6- regular deﬁcit drip irrigation with 50 percent crop water requirement (T6) in every irrigation period. Each experimental treatment includes four trees and 96 similar twelve years old trees overall. Cultivation practice was conducted similarly on all of the trees. Results and Discussion: Results showed that the highest yield and water use efficiency based on statistical analysis belong to both PRD treatments i.e. alternate partial root-zone drip irrigation with 100 percent crop water requirement and alternate partial root-zone flood irrigation with 100 percent crop water requirement, respectively, that both of them decreased water requirement for irrigation up to 35 and 50 percent in comparison tocontrol. Application of partial root drying irrigation on both traditional flood irrigation and drip irrigation, in comparison todeficit irrigation, caused a significant increment of water use efficiency up to 78.34 and 71.4 percent than control in pomegranate trees, respectively. Reduction of water consumption caused a significant increase on pomegranate fruit set and there was a significant positive correlation between pomegranate yield and fruit set percentage. Increment of water use efficiency, fruit set percentage and yield had significant effects on fruit quality such as aril color, total soluble solid, total acid, TSS/TA and fruits peel color, so that, with decrease in water consumption, these traits were improved. Reducing water consumption caused an induction in reproductive characteristics, meanwhile reduced vegetative growth that is dominated in pomegranate trees. Under partial root drying irrigation and deficit irrigation on both traditional flood irrigation and drip irrigation, due to the differentiation in root morphology and structure by positive hydrotropism, increment of water absorption and use efficiency could be improved in consequence. Decreasing amount of water inirrigation had significant effect on fruit quality. Fruit peel thickness and cracking had significant relationship with each other and fruit cracking has affected by deficit irrigation. The highest total soluble solid to acid of fruit juice belong to regular deﬁcit drip irrigation with 50 percent crop water requirement that caused an increment of 95.34 in comparison tocontrol. After that, alternate partial root-zone drip irrigation with 100 percent crop water requirement and flood irrigation with 100 percent crop water requirement as alternate partial root-zone irrigation caused an increment intotal soluble solid to acid ratioof fruit juice with 61.94 and 52.99 percent. The highest amount of TSS in pomegranate fruit juice belong to alternate partial root-zone drip irrigation with 100 and 50 percent crop water requirement with 20.51 and 18.01 percent increment than control treatment, respectively. Maximum amount ofacidity infruit juice belongs to full flood irrigation with 100 percent crop water requirement (control) and the minimum amount of thatbelong to regular deﬁcit drip irrigation with 50 percent crop water requirement. Conclusions: with regard to the irrigation management, the best applicable treatment for pomegranate cultivar Zarde-anar was alternate partial root-zone drip irrigation with 100 percent crop water requirement that could be recommended for the Arsenjan and same climate region. After that in the second place the alternative treatment were flood irrigation with 100 percent crop water requirement as alternate partial root-zone irrigation and followed with flood irrigation with 50 percent crop water requirement as regular deﬁcit irrigation, respectively.